10th annual London international advertising awards - Video Lab Group (Kew Garden Hills : Video Lab Group, 1995)
Shows the advertisement that have won the 10th annual London International Advertising Awards. Countries that have been took part were Europe, India, Pakistan, Middle East, Far East South America, Australia, Asia and South Africa
vol. 1. 1995 Winner reel - vol. 2. Humour - vol. 3. Banking/financial/insurance
Keywords: Advertising; Humor in advertising; Advertising -- Banks and banking